Soybean Flour Improves Fatty Acid Profile and Decreases Hepatic Triglyceride Deposition in Rats Fed with Normocaloric and Hypercaloric Diet - Razzeto, Gabriela Silvina (2015)
This study investigated the effects of replacing casein with soy flour on the fatty acids profile and triglycerides metabolism in the liver of rats that were previously fed with normocaloric and hypercaloric diets based on casein. Wistar male rats were used; one group was fed with control diet (AIN-93) and another with hypercaloric diet (AIN-93 with 34.15% sucrose, 42% fat calories) for 9 weeks. Each group was then divided into two subgroups and casein was replaced with soybean in one of them, obtaining CC (control casein), CS (control soy), HC (hypercaloric casein) and HS (hypercaloric soy), which were fed for 6 weeks. We measured triglycerides in serum, and triglycerides, total lipids, fatty acids profile, the expression of apolipoprotein B (Apo B), acetyl-CoA carboxylase (ACC), fatty acid synthase (FAS), sterol-regulatory element-binding protein 1c (SREBP-1c), mitochondrial glycerol-3-phosphate acyltransferase (mGPAT), diacylglycerol acyltransferase 2 (DGAT-2), carnitine palmitoyltransferase 1 (CPT-1) and peroxisome proliferator-activated receptors alpha (PPARα) in liver. Histological studies were also performed. When comparing HS vs. HC, a positive effect of soybean flour on hepatic triglycerides deposits was found, possibly through the reduction in DGAT-2 expression (P < 0.01) and the increase in Apo B (P < 0.001) expression. Soybean flour also decreased fat deposits in control diets when compared with casein, decreasing the DGAT-2 (P < 0.001) expression and increasing Apo B (P < 0.001), CPT-1 (P < 0.05) and PPARα (P < 0.01) expressions. Both soy diet subgroups increased unsaturated fatty acids respect to casein diets (P < 0.01). Hepatocytes showed few lipid droplets in HS, whereas a fat deposit in HC was observed. These results suggest that replacing casein with soybean flour in normocaloric and hypercaloric diets reduces triglycerides and improves fatty acids profile in rat liver.